Taking the edge off: a feasibility randomized controlled trial of an online mindfulness-based intervention to reduce suspiciousness/paranoia in high positive schizotypy - McDonald, Heather; Valmaggia, Lucia; Antonova, Elena; Chadwick, Paul (Frontiers in Psychology, 2024)
Positive schizotypy can uniquely predict the development of psychosis with suspiciousness/paranoia having emerged as a key risk factor, pointing to significant worth in reducing this aspect in individuals with high positive schizotypy. Reduced paranoia in the general population following brief online mindfulness training has been previously reported. This study investigated the feasibility of a 40-day online mindfulness-based intervention (MBI) (n = 12) in the individuals with high positive schizotypy characterised by high suspiciousness/paranoia and to estimate its effect on paranoia as compared with an active control condition using reflective journaling (n = 12). The outcome measures were self-reported trait and VR-induced state paranoia, completed at baseline, after 10 days and post-intervention. The feasibility criteria included retention, adherence, engagement, and acceptability. There was 100% retention, excellent adherence to content and engagement, with an average MBI session completion rate of 91%. Acceptability, indexed by a self-rated motivation to continue practice post-intervention, was also high. No MBI effect on trait paranoia was observed; however, the MBI group showed a reduction in the VR-induced state paranoia with a medium-to-large effect (d = .63). The findings support conducting larger-scale randomised controlled trials to evaluate the effects of online MBIs on reducing suspiciousness/paranoia to mitigate psychosis risk in individuals with high positive schizotypy. Trial registration: ISRCTN78697391 (ISRCTN registry, https://www.isrctn.com/).